2019
DOI: 10.1016/j.addbeh.2019.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ENDS advertising and use of marijuana in ENDS among college students

Abstract: Background-Factors associated with marijuana use in electronic nicotine delivery systems (ENDS) are largely unknown. ENDS advertising, through subtle normative cues as well as explicit and implicit messages suggesting ENDS products are socially condoned and healthier alternatives, may influence the use of marijuana in ENDS. The aim of our study was to examine the association between exposure to ENDS advertising and subsequent use of ENDS with marijuana among college students. Methods-Data for this study were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…Consistent findings are summarized here. Across studies, cannabis vaping was more common among males than females [ 21 , 24 , 28 , 29 , 47 , 170 , 173 , 178 , 179 , 182 , 185 , 198 , 200 ], and among older youth (e.g., high school compared to middle school students) in most studies [ 21 , 29 , 47 , 163 , 167 , 198 ], and among young adults compared to older adults [ 31 , 50 ]. Cannabis vaping was also more common among Hispanic youth compared with non-Hispanic White [ 28 , 163 , 167 , 190 ] or Black [ 21 , 28 , 167 , 190 , 198 ] youth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent findings are summarized here. Across studies, cannabis vaping was more common among males than females [ 21 , 24 , 28 , 29 , 47 , 170 , 173 , 178 , 179 , 182 , 185 , 198 , 200 ], and among older youth (e.g., high school compared to middle school students) in most studies [ 21 , 29 , 47 , 163 , 167 , 198 ], and among young adults compared to older adults [ 31 , 50 ]. Cannabis vaping was also more common among Hispanic youth compared with non-Hispanic White [ 28 , 163 , 167 , 190 ] or Black [ 21 , 28 , 167 , 190 , 198 ] youth.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed greater socio-economic status (SES) may be a risk factor for cannabis vaping [ 24 , 47 , 64 , 170 , 182 ]. E-cigarette use with nicotine only or flavors [ 28 , 29 , 163 , 166 , 172 174 , 180 , 186 , 197 •, 198 , 200 ], as well as use of cigarettes, cigars, hookah, and smokeless tobacco [ 21 , 28 , 29 , 50 , 163 , 166 , 174 , 178 , 179 , 186 , 195 , 197 •, 199 ] is associated with greater odds of cannabis vaping. Former cannabis use, susceptibility to use cannabis, and peer use of cannabis, via vaping and other forms of cannabis consumption (e.g., ingesting, smoking), have also been shown to be related to greater odds of cannabis vaping [ 21 , 169 , 170 , 173 , 175 , 179 , 180 , 184 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a cohort study found that the trajectories of nicotine and cannabis vaping frequencies increased similarly over time in youth aging up into adulthood ( Lanza et al, 2020 ). These similarities in use patterns may derive from common risk factors such as EVP marketing/advertising strategies that may promote cannabis vaping in addition to nicotine ( Kreitzberg et al, 2019 ). While studies have evaluated cannabis vaping among adult populations, they often do not consider the possible intersection between nicotine and cannabis vaping ( Baldassarri et al, 2020 , Braymiller et al, 2020 , Pokhrel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%